Hydrogen Sulfide-Negative Variant of Citrobacter - Washington, John A. (1970)
The characteristics of 25 hydrogen sulfide-negative strains of Citrobacter were studied. The majority of isolates were from the respiratory tract and usually were of indeterminate clinical significance. All strains were highly susceptible to polymyxin B, gentamicin, kanamycin, nalidixic acid, and nitrofurantoin.